Detection of available phosphorus and diversity of culturable phosphate-solubilizing bacteria after organic farming conversion (Asian Journal of Agriculture, 2024)
Abstract. Waithaisong K. 2024. Detection of available phosphorus and diversity of culturable phosphate-solubilizing bacteria after organic farming conversion. Asian J Agric 8: 124-133. Organic Agriculture (OA) has increased in Thailand since 2000. Most studies on OA in Thailand focus on socio-economic sectors. Soil properties and microorganisms in OA soils have been little explored. This study aimed to investigate the soil nutrient status nitrogen (N), phosphorus (P), and biodiversity of Phosphate-Solubilizing Bacteria (PSB) in OA soils. Topsoil samples were collected from two organic paddy soils (OS1 and OS2). The soils were analyzed for particle distribution, cation exchange capacity, exchangeable elements, Organic Matter (OM), electrical conductivity, pH, N content, and P content. Soil bacteria were isolated on LB agar medium and screened for PSB on NBRIP agar. The sequences of the 16S rRNA gene were used to identify PSB. The results showed that in all the sites, soils were silty clay, and high accumulation of OM, high N availability, and ammonium was the main form of N. Phosphorus was present in low concentration indicating the limitation of P may reduce the nitrification process, while organic P was mostly found in soil. Analysis of microbial P revealed that P was mainly found in microbial cells of OS2. PSB identification showed that the main PSB genera found in OA soils were Enterobacter, Pantoea, Bacillus, and Pseudomonas. All results indicated that OS1 and OS2 soils had low P which affected N cycling. The reduction of P may result from the conversion of rice soil to organic agricultural practices. Further, PSB should be characterized and applied with rock phosphate in OA soils to maintain rice productivity.
Keywords: Organic farming, paddy soil, phosphate-solubilizing bacteria, phosphorus limitation, soil properties